2021
DOI: 10.3390/vaccines9060576
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Injury after COVID-19 Vaccine—A Case Report

Abstract: The COVID-19 pandemic has caused more than 3 million deaths worldwide. Recently developed genetically engineered vaccines are the most critical solution for controlling the pandemic. Clinical trials on a large number of participants confirmed their safety and efficacy. However, with the growing number of vaccinated people, new infrequent adverse effects have been reported, not described in the medicinal product characteristics. We would like to report a case of acute pancreatic injury that occurred shortly aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 13 publications
0
46
0
3
Order By: Relevance
“…Walter et al reported a case of acute necrotizing pancreatitis 10 h after the administration of the second dose of Pfizer-BioNTech COVID-19 mRNA vaccine in a 43-year-old male [ 13 ]. Cieslewicz reported a case of AP injury 20 h after Pfizer-BioNTech COVID-19 mRNA vaccination in a 29-year-old female [ 14 ]. As in the latter two cases, our patient presented mild AP shortly after receiving the vaccination without signs or symptoms of an allergic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Walter et al reported a case of acute necrotizing pancreatitis 10 h after the administration of the second dose of Pfizer-BioNTech COVID-19 mRNA vaccine in a 43-year-old male [ 13 ]. Cieslewicz reported a case of AP injury 20 h after Pfizer-BioNTech COVID-19 mRNA vaccination in a 29-year-old female [ 14 ]. As in the latter two cases, our patient presented mild AP shortly after receiving the vaccination without signs or symptoms of an allergic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable expression of ACE2 in human pancreatic islets has been reported. In patients with severe COVID-19, the expression of ACE2 inside the pancreas at some levels can cause acute inflammation which prompted acute pancreatitis [16].…”
Section: Underlying Pathogenesis Of Pancreatic Injurymentioning
confidence: 99%
“…Post-authorization monitoring has proven that adenoviral vector and mRNA-based vaccines are generally safe. However, various rare side effects were reported, including myocarditis, pericarditis [ 5 , 6 ], appendicitis [ 7 ], liver [ 8 ], pancreatic [ 9 ] and kidney injuries [ 10 ], and thrombotic thrombocytopenia [ 11 , 12 ]. The exact mechanisms behind these events require further investigations, although several potential explanations were offered [ 5 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%